Maghemite nanoparticles stabilize the protein corona formed with transferrin presenting different iron-saturation levels. Issue 34 (21st August 2019) - Martens, Ulrike; Böttcher, Dominique; Talbot, Delphine; Bornscheuer, Uwe; Abou-Hassan, Ali; Delcea, Mihaela
Abstract : Maghemite nanoparticle-transferrin corona formation depends on the protein–iron-loading and the protein is stabilized by bioconjugation. Abstract : Magnetic nanoparticles are ideal candidates for biomedical applications given their potential use in magnetic resonance imaging, magnetic hyperthermia and targeted drug delivery. Understanding protein–nanoparticle interactions in the blood stream is of major importance due to their potential risks, especially immunogenicity ( i.e. the ability to induce an immune response). Here, we report on the interaction of superparamagnetic maghemite (γ-Fe2 O3 ) nanoparticles with human blood plasma protein transferrin presenting different iron-saturation levels: partially iron-saturated ( i.e. transferrin) and iron-free transferrin ( i.e. apotransferrin). The nanoparticle–protein interaction and the protein corona formation were studied using biophysical and chemical approaches based on dynamic light scattering, gel electrophoresis, circular dichroism spectroscopy and differential scanning fluorimetry. We found that iron content governs the protein corona formation and induces a strong effect on the thermal stability of the bound protein. Our results demonstrate a stabilizing effect of the nanoparticles with a change of the unfolding position of approximately 10 °C towards higher temperatures for transferrin. Our study may be relevant for the further development of magnetic nanoparticles as diagnostic and therapeutic tools.